Extreme Ophthalmomyiasis externa with simultaneous facial and scalp involvement - Ali Rizvi, Syed Wajahat; Akram, Sardar Mohd; Ashraf, Humayoun; Siddiqui, Mohammed Azfar (Nepalese Journal of Ophthalmology, 2016)
Background: Ophthalmomyiasis is a rare entity seen mainly in immunocompromised host with neglected wounds under poor hygienic conditions. Case: We report a case of extreme ophthalmomyiasis with extensive facial and scalp involvement in an old rural inhabitant following evisceration. Conclusion: Proper wound care and personal hygiene are of paramount importance for good wound healing. Nepal J Ophthalmol 2016; 8(15): 95-96